The role of social protection in environmental fiscal reforms - Daniele Malerba (German Institute of Development and Sustainability (IDOS), 2023)
Socio-ecological transitions need to address the pressing challenges of our time, namely climate change mitigation and social development - including poverty and inequality reduction - in a complementary manner. The importance of achieving resilient and sustainable societies has been made more evident by recent shocks such as the Covid-19 pandemic and the war in Ukraine. As a consequence, national and international development policies need to foster links between social and environmental goals and policies. One way to achieve such synergies is through environmental fiscal reforms, defined as the combination of carbon-pricing mechanisms and consequent revenue spending for environmental and socio-economic goals. Even though carbon pricing is just one of the instruments needed to achieve climate goals, it provides the complementary benefit of expanding revenues while incentivising a reduction in emissions though market signals. This paper discusses environmental fiscal reforms from the perspective of low- and middle-income countries and development cooperation, with a focus on how to improve the social outcomes of such reforms. While revenues can be recycled for different purposes - including compensating industries with high adaptation costs, further investments in environmental projects and research, and use for the general budget - the paper focusses on social spending. The revenue can be used to decrease poverty and inequality levels and to compensate the poorest for increases in prices by utilising social protection mechanisms. This is particularly important to garner broad societal support and to make environmental fiscal reforms and carbon pricing more socially acceptable and implementable at sufficient levels in more countries. The paper first presents the key features of different carbon-pricing policies and the revenues they can generate, especially for low- and middle-income countries that have limited fiscal space. It then shows how the revenue can be used to fund social protection mechanisms that can compensate the poorest and address distributional concerns. It underlines the gaps and limitations of current social protection programmes, especially in terms of low coverage of vulnerable populations. This also constrained the response to the war in Ukraine, as lower-income countries had to use price stabilisation mechanisms - which ultimately generated negative fiscal and environmental effects - to avoid inflicting greater burdens on the poor instead of providing targeted programmes. The paper also offers some design principles to best address distributional concerns, including sequencing and sectoral coverage. It then discusses the role that development cooperation can have in implementing environmental fiscal reforms in low- and middle-income countries. Overall, the paper suggests that environmental fiscal reforms can be used to achieve resilient societies and accelerate the fight against climate change, with the goal of building a more inclusive and sustainable future. Such reforms should become a priority of German development cooperation and a key lever for its strategic goals, instead of occupying a peripheral role, as it currently does. Most importantly, the analysis strongly underlines the case for environmental fiscal reforms rather than the current use of subsidies and price controls; this is true when considering both climate goals (as keeping prices low does not incentivise shifts in production and consumption) as well as social goals (e.g. cash transfers result in significantly greater levels of poverty and inequality reduction when compared to untargeted subsidies). Therefore, social protection investments are urgently needed, also in lower-income countries. The current energy crisis due to the war in Ukraine and the Covid-19 pandemic has made this clearer.
Keywords: 330; climate change; social security and inclusion